A toxina urêmica ácido guanidinicoacético inibe o metabolismo oxidativo dos neutrófilos de cães - Pereira, Priscila Preve [UNESP]; Bosco, Anelise Maria [UNESP]; De Almeida, Breno Fernando Martins [UNESP]; Narciso, Luis Gustavo [UNESP]; Ciarlini, Paulo César [UNESP] (FapUNIFESP (SciELO), 2015)
Among the uremic toxins proven to affect the neutrophil function in humans with chronic kidney disease (CKD), guanidine compounds stand out. To achieve a clearer understanding of the mechanisms that affect the immunity of uremic patients, the hypothesis that guanidine acetic acid (GAA) contributes to the inhibition of oxidative metabolism and an increase in neutrophil apoptosis in healthy dogs was investigated in vitro. To this end, neutrophils isolated from ten healthy dogs were incubated in pure RPMI 1640 (control) and enriched with 5 mg/L of GAA. Capillary flow cytometry was used to quantify superoxide production in neutrophils with the probe (hydroethidine), in the presence and absence of phorbol-12-myristate-13-acetate (PMA), in order to assess oxidative metabolism. Apoptotic indices were quantified using the Annexin V-PE system, with and without the inductive effect of camptothecin. Neutrophils isolated and incubated in a GAA-enriched medium produced smaller amounts of superoxide (p < 0.001) when activated with PMA, however, this inhibition of oxidative metabolism occurred without significantly altering their viability or rate of apoptosis. Thus, the results show guanidine compounds contribute to immunosuppression in dogs with CKD.
Uremic toxin guanidine acetic acid inhibits the oxidative metabolism of neutrophils in dogs
Keywords: Kidney failure; Respiratory burst; Superoxide; Uremia